2007
DOI: 10.1177/0163278706297333
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Patient Communication Skills to Medical Students

Abstract: Tools to examine the effects of teaching interventions across a variety of studies are needed. The authors perform a meta-analysis of 24 randomized controlled trials evaluating the effects of teaching on medical students' patient communication skills. Study quality is rated using a modified Jadad score, and standardized mean difference effect size (d) measures are calculated. Fifteen of 24 studies have sufficient data for analysis. Students' ability to establish rapport improves after teaching. The effects are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 28 publications
1
55
1
1
Order By: Relevance
“…Moreover, a meta-analysis of 24 randomised controlled trials evaluating the effects of teaching interventions on medical students' patient communication skills showed that the two most effective teaching methods in improving student performance were direct feedback on a student-patient interview and small-group discussions. 7 However, none of the studies in the metaanalysis included student psychotherapy schemes or Balint groups, and we believe our study to be the first reported randomised controlled trial of these teaching methods, both of which revolve around small-group discussion and detailed feedback regarding the student's direct contact with patients, from either the student's supervisor in the case of the SPS or from the Balint group leader.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, a meta-analysis of 24 randomised controlled trials evaluating the effects of teaching interventions on medical students' patient communication skills showed that the two most effective teaching methods in improving student performance were direct feedback on a student-patient interview and small-group discussions. 7 However, none of the studies in the metaanalysis included student psychotherapy schemes or Balint groups, and we believe our study to be the first reported randomised controlled trial of these teaching methods, both of which revolve around small-group discussion and detailed feedback regarding the student's direct contact with patients, from either the student's supervisor in the case of the SPS or from the Balint group leader.…”
Section: Discussionmentioning
confidence: 98%
“…Many of the studies attempting to evaluate different methods for teaching communication skills lack a control group, 7 and often the main measurement is based on the student's own self-evaluation, which does not correlate with other measures, such as evaluation by their teachers, and may not be indicative of actual improvement as poorly performing students tend to overrate their ability. 8,9 Psychodynamic teaching at University College London School of Medicine…”
mentioning
confidence: 99%
“…19,80 Small group sessions are generally perceived positively by attendees, 6,71,77 and a recent meta-analysis has suggested that this modality is highly efficient in improving communication skills in medical students. 81 …”
Section: Small Groups and Workhopsmentioning
confidence: 99%
“…[20][21][22][23] Research in radiology, critical care management, nursing, and family medicine has provided empirical evidence that formative feedback leads to significant improvements in skills acquisition. [24][25][26][27][28] In our study, the subjects were all learners at a very early stage in their medical education, and when these virtually laylearners were given formative feedback on videotaped performance of a learned skill, they showed similar improvement in skill retention to that demonstrated by advanced learners. [24][25][26][27][28] There is a paucity of data regarding BLS skills learning using videotape reviewing and feedback.…”
Section: Discussionmentioning
confidence: 85%
“…[24][25][26][27][28] In our study, the subjects were all learners at a very early stage in their medical education, and when these virtually laylearners were given formative feedback on videotaped performance of a learned skill, they showed similar improvement in skill retention to that demonstrated by advanced learners. [24][25][26][27][28] There is a paucity of data regarding BLS skills learning using videotape reviewing and feedback. Two previous studies about infant BLS found that acquisition of skills after CPR training by truly layrescuers varied from 33% to 72.5% with traditional teaching methods 8 and was 38% with self-directed learning using videotapes.…”
Section: Discussionmentioning
confidence: 85%